Attività sportiva e COVID-19: cosa c'è di nuovo? - Elisa Lodi; Giovanni Lodi; Letizia Reggianini; Gustavo Savino; Maria Grazia Modena (2021)
Growing evidence about COVID-19 and its possible cardiopulmonary complications have raised concerns about a potential subclinical heart damage even in asymptomatic patients. Many countries worldwide provided recommendations for a safe return to play and sports activity for athletes with previous COVID-19 disease. Italy was among the first nations to deal with the problem of protecting athletes’ health. In this regard, after an initial version released on April 2020, on December 11, 2020 the Italian Sports Medicine Federation (FMSI) updated the recommendations for the return play of non-professional athletes. The purpose of this article is to analyze and deepen the contents of the new FMSI recommendations, integrating and comparing them with the previous ones. Further updates may occur if new scientific and epidemiological evidence will rise regarding COVID-19. Growing evidence about COVID-19 and its possible cardiopulmonary complications have raised concerns about a potential subclinical heart damage even in asymptomatic patients. Many countries worldwide provided recommendations for a safe return to play and sports activity for athletes with previous COVID-19 disease. Italy was among the first nations to deal with the problem of protecting athletes’ health. In this regard, after an initial version released on April 2020, on December 11, 2020 the Italian Sports Medicine Federation (FMSI) updated the recommendations for the return play of non-professional athletes. The purpose of this article is to analyze and deepen the contents of the new FMSI recommendations, integrating and comparing them with the previous ones. Further updates may occur if new scientific and epidemiological evidence will rise regarding COVID-19.